Emotional Scenes as Context in Emotional Expression Recognition: The Role of Emotion or Valence Match - Bryce, L.; Mika, G.; Craig, B.M.; Hess, U.; Lipp, Ottmar (2024)
Emotion recognition is influenced by contextual information such as social category cues or background scenes. However, past studies yielded mixed findings regarding whether broad valence or specific emotion matches drive context effects and how multiple sources of contextual information may influence emotion recognition. To address these questions, participants were asked to categorize expressions on male and female faces posing happiness and anger and happiness and fear on pleasant and fearful backgrounds (Experiment 1, conducted in 2019), fearful and disgusted expressions on fear and disgust eliciting backgrounds (Experiment 2, conducted in 2022), and fearful and sad expressions on fear and sadness eliciting backgrounds (Experiment 3, conducted in 2022). In Experiment 1 (where stimuli varied in valence), a broad valence match effect was observed. Faster recognition of happiness than fear and anger was more pronounced in pleasant compared to fearful scenes. In Experiments 2 and 3 (where stimuli were negative in valence), specific emotion match effects were observed. Faster recognition occurred when expression and background were emotionally congruent. In Experiments 1 and 3, poser sex independently moderated emotional expression recognition speed. These results suggest that the effect of emotional scenes on facial emotion recognition is mediated by a match in valence when broad valence is task-relevant. Specific emotion matches drive context effects when participants categorize expressions of a single valence. Looking at the influence of background contexts and poser sex together suggests that these two sources of contextual information have an independent rather than an interactive influence on emotional expression recognition speed.